The multicultural prison ethnicity, masculinity, and social relations among prisoners - Phillips, Coretta (Oxford : Oxford University Press, 2013)
This work presents a unique sociological analysis of the negotiation of ethnic difference within the closed world of the male prison. Using rich empirical material drawn from extensive qualitative research in Rochester Young Offenders' Institution and Maidstone prison, the author provides an arresting insight into how race is written into prison relations.
Series from CIP print record.
Specialized.
Description based on online resource; title from home page (viewed on Dec. 20, 2012).
Includes bibliographical references and index.
Keywords: Prisons -- Great Britain -- Sociological aspects; Prisons and race relations -- Great Britain; Masculinity -- Social aspects; Prison psychology -- Great Britain; HMYOI Rochester; HM Prison Maidstone; True Crime; Social services & welfare, criminology